1989
DOI: 10.1148/radiology.172.3.2672092
|View full text |Cite
|
Sign up to set email alerts
|

Siderotic nodules in the spleen: MR imaging of portal hypertension.

Abstract: The authors retrospectively evaluated magnetic resonance (MR) images obtained at 1.5 T in 233 patients with portal hypertension and 91 subjects without it and pathologic findings in four resected spleens (one normal). Multiple, tiny (3-8 mm in diameter), low-intensity spots in the spleen were observed in 21 of 233 patients. Among the imaging studies performed in these 21 patients, the spots were seen on five of 14 T1-weighted images, 11 of 20 proton density images, and 12 of 20 T2-weighted images obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…These granulomas tend to be larger and more hyperechogenic than siderotic nodules, besides presenting an evident acoustic shadowing, a feature that is not present in the case of non-calcified siderotic nodules (9) , which represented the majority in the present study. Additionally, because of the paramagnetic effect of hemosiderin products, siderotic nodules are clearly visualized on T1-and T2-weighted images as small foci of low-intensity or absent signal and without contrast-enhancement after intravenous gadolinium injection (9,10) .…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…These granulomas tend to be larger and more hyperechogenic than siderotic nodules, besides presenting an evident acoustic shadowing, a feature that is not present in the case of non-calcified siderotic nodules (9) , which represented the majority in the present study. Additionally, because of the paramagnetic effect of hemosiderin products, siderotic nodules are clearly visualized on T1-and T2-weighted images as small foci of low-intensity or absent signal and without contrast-enhancement after intravenous gadolinium injection (9,10) .…”
Section: Resultsmentioning
confidence: 48%
“…Conversely, non-calcified tuberculotic nodules tend to present a variable signal on T1-and T2-weighted images, and most frequently with hyper-intense signal and ring-shaped contrast-enhancement after gadolinium injection (24) . Calcified siderotic nodules may not be distinguishable from different types of calcified granulomas, like those resulting from tuberculosis and histoplasmosis (9) . Amongst the limitations of the present study, it is important to note the restricted number of patients included in the sample, as well as the absence of a control group which would allow the addition of other useful information (for example, specificity, positive and negative predictive values) for determining the US diagnostic accuracy in the detection of these nodules.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…They are due to areas of organized hemorrhage and histologically contain hemosiderin and sometimes also calcification. 15,16 A recent prospective study found that sonography had a sensitivity of 71% for Gamna-Gandy bodies. 17 On sonography, Gamna-Gandy bodies appear as small hyperechoic foci, 17 similar in appearance to the echogenic foci seen in the ovaries.…”
mentioning
confidence: 99%